Corporate Reputation as a Strategic Management Tool: Through the Lens of Employees - Esenyel, Vildan (International Journal of Management and Sustainability, 2020)
As a result of the relationship with corporate reputation and financial facets, the role of employees in reputation management should be profoundly analyzed. In this sense, in this study, it is aimed to reveal the usefulness of the corporate reputation, which is called as a vital competition tool for the institutions, to the human resources to keep the qualified workforce, which has become one of the most critical problems of the enterprises. How employees see the company is reflected, other stakeholders therefore, it is necessary to examine the perception of the reputation of a company from the perspective of its employees. Through the critical analysis of corporate reputation literature, it is aimed to help the empirical research on corporate reputations. As a lack of related literature, a comprehensive literature review presents conceptual background information on reputation and the findings at the individual level provide input to all firms that give importance to the issue of corporate reputation, as well as the academic contribution to corporate reputation and strategic management literature.